Implementation Of Social Safety Net Policies For Vulnerable Groups - Imam Hanafi (Publikasi Indonesia, 2023)
This study aims to analyze social safety net policies for vulnerable groups in the face of an economic downturn due to the Covid-19 pandemic. They are also analyzing whether policies during a pandemic can protect vulnerable workers. Data collection is done by literature study and secondary data. The research results show that social safety net policies during the pandemic were still unable to save the people's economy fully. During the COVID-19 pandemic, several social safety net programs presented new problems at the implementation level, especially at the grassroots level. Some problems that arise are the uneven distribution of aid distribution, uncertainty of procedures and requirements for receiving assistance, data on target recipients that are not up-to-date, emergency conditions of residents who need them but are not registered, and problems of informal sector workers who are migrants. The government needs to review the social safety net policy and improve poverty data to be integrated